Idiopathic serontonin syndrome. Can we prevent it? - L. Gallardo Borge; I.D.L.M. Santos Carrasco; P. Marqués Cabezas; L. Rodriguez Andrés; A. Rodriguez Campos (European Psychiatry, 2022)
Introduction Serotonin syndrome is a mild to potentially life-threatening syndrome associated with excessive serotonergic activity within the central nervous system. Serotonin syndrome is associated with medication use, drug interactions and overdose. All drugs that increase central serotonin neurotransmission at postsynaptic 5-HT1A and 5-HT 2A receptors can produce SS.